Geochemical and Sr-Nd isotopic variations in a deep-sea sediment core from Eastern Indian Ocean: Constraints on dust provenances, paleoclimate and volcanic eruption history in the last 300,000years - Liu, E.; Wang, Xuan-Ce; Zhao, J.; Wang, X. (Elsevier, 2015)
This study reported geochemical and Sr–Nd isotopic variation of fine-grained mineral components in a deep-sea piston core G6-4, south of the Sumba Island, Eastern Indian Ocean. The new data enables us to characterize dust contributions from Australian continent and volcanic eruption history in the adjacent volcanic arc over approximately the last 300,000 years. The geochemical and isotopic features of the fine-grained components (< 20 μm) in Core G6-4 are broadly consistent with mixing between aeolian dusts from the Australian continent and volcanic ashes of the Sunda arcs. Simple two-component modeling shows that the majority of the core samples probably are composed of 50–80% aeolian dusts derived from the Australian continent. Sr–Nd isotopic ratios are fairly uniform for samples older than 180 ka, in contrast with those of the samples younger than 180 ka, which are much more variable with three anomalies characterized by higher 143Nd/144Nd and lower 87Sr/86Sr values recognized. We interpret the three anomalies in the last 80 ka as recording episodes of eruptions from nearby volcanoes. Thus, it is likely that volcanism become more active in the last 80 ka. Excluding these anomalies, the average 143Nd/144Nd was generally lower, and average 87Sr/86Sr was higher in the post-180 ka section than in the older section, which might be associated with increased Australian continental aridity toward more recent time.